Walking Propositions: Coming to Know A/r/tographically. (21st August 2019) - Lee, Nicole; Morimoto, Ken; Mosavarzadeh, Marzieh; Irwin, Rita L.
Abstract: This article explores walking as a form of inquiry within a study group at The University of British Columbia committed to a/r/tography. Three propositions are explored and as a result we think more deeply about being present, truly present, to that which we never anticipated. The first proposition, 'Go for a walk outside, find an object and do something with it', leads us to think more deeply about being present to possibility: kicking the rock. The second proposition, 'Walk around your neighbourhood with another. When you find unfamiliar ground, pause, and ground yourself', leads us to appreciating being present in‐between place and relationality. The third proposition, 'Follow one another in a line without stopping or speaking', invites us to explore being present to interiority. Walking in response to these propositions and coming to think deeply about the impact of being present to presence, became important to us as a community of a/r/tographers.